The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1038/mp.2014.24
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological mechanism underlying antidepressant effect: a systematic meta-analysis

Abstract: Antidepressants are widely used in clinical practice for the treatment of depression and other mood disorders. Numerous neuroimaging studies have recently examined how antidepressants influence emotional processes. However, both clinical trials and neuroimaging studies have reported inconsistent responses to antidepressants. Moreover, the neuropsychological mechanisms by which antidepressants act to improve depressive features remain underspecified. This systematic meta-analysis summarizes pharmacological neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
177
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(211 citation statements)
references
References 65 publications
(88 reference statements)
15
177
1
1
Order By: Relevance
“…Notably some patients may also be on anxiolytic or antidepressant medication, likely to alter affective processing [70].…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Notably some patients may also be on anxiolytic or antidepressant medication, likely to alter affective processing [70].…”
Section: Methodological Issuesmentioning
confidence: 99%
“…This has critical implications in the translation of the oxytocin effect from animal models to clinical populations, and draws caution to map animal findings directly on to human neurobiology. In addition, our previous work has documented genetic modulation on pharmacological challenge (ie, serotonin transporter gene modulated the efficiency of serotonergic drugs; Ma, 2015;Ma et al, 2015); therefore, it is of critical interest for future research to further test how psychological and biological factors influence the effects of oxytocin.…”
Section: Discussionmentioning
confidence: 99%
“…B 370: 20140213 also found decreased amygdala response to fearful faces [30,39,41,42]. However, other studies have found increased amygdala response [43], and a recent meta-analysis showed that the direction of effects in this network of structures varies between studies [46]. Future work should attempt to establish the reason behind these discrepancies, including a focus on dose-response relationships and the basal characteristics of the volunteers included in the studies.…”
Section: (I) Short-term Administrationmentioning
confidence: 99%
“…These patterns of neural activity, restricted to areas involved in relatively low-level processing of emotional stimuli, suggest that early effects of antidepressants may be working in a 'bottom-up' fashion, affecting the automatic evaluation of emotional stimuli [45]. Indeed, a recent meta-analysis found that across a range of different cognitive tasks, short-term antidepressant treatment increased activation to positive emotional information, and decreased activation to negative information, across a network including the amygdala, putamen, ACC, parahippocampal gyrus and medial prefrontal cortex [46]. These limbic and paralimbic structures are involved in detecting and responding to salient emotional information, supporting this 'bottom-up' interpretation of early antidepressant effects.…”
Section: (I) Short-term Administrationmentioning
confidence: 99%